Biodegradable packaging materials based on low density polyethylene, starch and monoglycerides - I. Yu. Vasilyev; V. V. Ananyev; M. E. Chernov (Тонкие химические технологии)
Objectives. To investigate the production and biological degradation of biodegradable hybrid compositions (BHCs), dispersed-filled with starch-containing products of various origins and distilled monoglycerides, along with the biodegradation of compositions based on low density polyethylene and thermoplastic starch (TPS) of various origins: corn, pea, and rice.Methods. Thermoplastic starch was obtained based on native starches of several types, which were processed in Brabender and MashkPlast (Russia) laboratory extruders. BHCs in the form of strands, granules, and films were obtained by mixing thermoplastic starches with polyethylene in extruders. Structural BHC parameters were studied by optical and electron scanning microscopy. The biodegradability of the composite films was evaluated by placing them in biohumus for six months; during storage, the change in water absorption of the films was determined. Before and after the biodegradation process, tensile fracture stress and elongation at rupture were determined to evaluate BHC performance (physical and mechanical characteristics of films). Changes in the chemical structure during biodegradation were determined by Fourier infrared spectroscopy.Results. The positive effect (acceleration of the biodegradation process) of using a novel type of starch plasticizer—monoglycerides distilled in TPS–polyethylene compositions—was confirmed. After six months, intensive sporulation of active microorganisms was observed on the surface of the samples. At the same time, water absorption by the samples reached 30%. The observed 60% decrease in strength and deformation properties indicates an intensive process of biodegradation.Conclusions. The biodegradation rate was shown to depend on the concentration and even distribution of the natural biodegradable filler in the synthetic polymer composition.